Beetroot (Beta Vulgaris L) Juice on Hemoglobin Levels in Pregnancy - Shinta Novelia; Jenny Anna Siauta; Cucu Halimatusyadiah; Orachorn Lumprom (KHD Production, 2025)
Malnutrition, iron deficiency, malabsorption, and chronic illness are the direct causes of anemia. There was already a non-pharmacological treatment for anemia in pregnancy, such as eating green vegetables, beans, chicken liver, beetroot, and red guava fruit. Beets have one of the highest quantities of folic acid of any fruit, at 108 mg, compared to other fruits. The goal of this study was to see how beetroot juice (Beta vulgaris L) affected hemoglobin levels in anemic pregnant women at the Cibatu Health Center in Garut Regency. The approach is a quasi-experimental investigation. The population was made up of 234 pregnant women in their third trimester. Purposive sampling was used in this study, with 48 persons separated into the experimental and control groups. Observation sheets and Easy Touch GCHb were used as instruments. Paired T-test and Independent Samples Test were used to analyze the data. The results demonstrate that before being given beet juice, the average hemoglobin level in the experimental group was 9.09. After being given beetroot juice, it was 10,98 while in the control group. Observation sheets and Easy Touch GCHb were used as instruments. Paired T-test and Independent Samples Test were used to analyze the data. The results show that before being given beet juice, the average hemoglobin level in the experimental group was 9.09, and after being given beetroot juice was 10,98. In contrast, in the control group, the hemoglobin level of the first examination was 8.99, and the hemoglobin level of the second examination was 9.92. The p-value for the bivariate analysis between and within groups was 0.000 (0.05). It can be inferred that beetroot juice affects hemoglobin levels in anemic pregnant women. This finding is predicted to help boost hemoglobin levels in pregnant women who have anemia.